2022
DOI: 10.1098/rsif.2022.0258
|View full text |Cite
|
Sign up to set email alerts
|

Active anemosensing hypothesis: how flying insects could estimate ambient wind direction through sensory integration and active movement

Abstract: Estimating the direction of ambient fluid flow is a crucial step during chemical plume tracking for flying and swimming animals. How animals accomplish this remains an open area of investigation. Recent calcium imaging with tethered flying Drosophila has shown that flies encode the angular direction of multiple sensory modalities in their central complex: orientation, apparent wind (or airspeed) direction and direction of motion. Here, we describe a general framework for how these three… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…In both laminar wind and still air, immediately after odor onset, flies decelerate and often perform a rapid turn. Both maneuvers are consistent with predictions from recent control theoretic analyses for how insects may estimate properties of wind while in flight 7, 8 . We suggest that flies may use their deceleration and “anemometric” turn as active sensing maneuvers to rapidly gauge properties of their wind environment before initiating a proximal or upwind search routine.…”
supporting
confidence: 86%
See 3 more Smart Citations
“…In both laminar wind and still air, immediately after odor onset, flies decelerate and often perform a rapid turn. Both maneuvers are consistent with predictions from recent control theoretic analyses for how insects may estimate properties of wind while in flight 7, 8 . We suggest that flies may use their deceleration and “anemometric” turn as active sensing maneuvers to rapidly gauge properties of their wind environment before initiating a proximal or upwind search routine.…”
supporting
confidence: 86%
“…Additionally, because angular velocity measurements twice propagate the derivatives of tracking noise from flies' x and y position, we found that angular velocity estimates on occasion experience brief highly variable segments along a trajectory. To account for this in our angular velocity analyses, we implemented a Butterworth Filter on the trajectory course direction before first order finite differentiation, all implemented in Python using the PyNumDiff package [Van Breugel et al, 2022].…”
Section: Trajectory Inclusion Criteria and Data Filteringmentioning
confidence: 99%
See 2 more Smart Citations
“…Brief bursts of saccades in the same direction may aid local search strategy by allowing the animal to quickly scan the local environment for salient visual and olfactory features (Heisenberg and Wolf, 1984). More recently, it has been suggested that comparing sensory measurements before and after each saccade might enable flies to estimate key parameters that are otherwise not directly measurable, such as the direction and magnitude of the ambient wind (van Breugel et al, 2022). For all these hypotheses, the timing between saccades is critical, and several factors are thought to influence the frequency of the spontaneous turns.…”
Section: Introductionmentioning
confidence: 99%